Porosity and Permeability Study of the Mundu Formation Limestone Unit as a Potential Reservoir Rock in the Gunung Pegat Area, Bojonegoro, East Java - Amri, Danang; Siti Umiyatun; Wahyuni Annisa Humairoh; Kharisma Idea; Samuel Antonio Gutteres; Muhammad Ferdian Yusuf (Jurnal Offshore: Oil, Production Facilities and Renewable Energy, 2025)
This research was conducted in the Gunung Pegat area, Babat District, Bojonegoro Regency, East Java. The geographical coordinates of the research location are from 7°7′31″ to 7°8′11″ South Latitude and 112°9′46″ to 112°8′54″ East Longitude. Geologically, it is part of the Rembang Zone and is composed of the Mundu Limestone Formation. The research location is one of the sites that shows an outcrop of the Mundu Formation, with limestone lithology that has the potential to be a reservoir rock. The objective of the research is to study the porosity and permeability characteristics and to evaluate the potential of the limestone as a reservoir rock. The methods used include geological mapping, rock sampling, calcimetry analysis, petrographic analysis, and determination of porosity and permeability values. The results show that the geomorphological units of the research area are divided into anthropogenic, karstic, and fluvial landforms. The rock units at the research location are divided into a limestone unit and a fluvial unit; specifically, the limestone is classified as packstone and wackestone based on calcimetry and petrographic analysis. The stratigraphic sequence from the oldest to the youngest is the Miocene-aged Mundu Limestone Unit and the Holocene-aged Alluvial Unit. The average porosity value of the research area is 30.38%, which falls into the 'excellent' category, and the permeability value is 236.70 mD, which is classified as 'very good,' indicating that the research area has potential as a reservoir.